Cui Bono: Do Open Source Software Incubator Policies and Procedures Benefit the Projects or the Incubator?. Issue 1 (29th April 2022) - Sen, Anamika; Atkisson, Curtis; Schweik, Charlie
Open source software (OSS), a form of Digital or Knowledge Commons, underlies much of the technology that we use in our daily lives. The existence and continuation of OSS relies on the contribution of private resources – personal time, volunteer energy, and effort of numerous actors (e.g., software developers' time as a common-pool resource) – to public goods, the benefits of which are enjoyed by everyone. Nonprofit organizations such as the Apache Software Foundation (ASF) attempt to aid this process by providing various collective services to OSS projects, acting as a second-order actor in the production of the public good. To this end, the ASF Incubator has created policies – essentially rules or norms – that serve to protect its interests and, as they say, increase the sustainability of the projects. Each policy requires investment by ASF (in terms of money or the use of volunteer time) or an incubating project (in terms of taking project personnel time), the benefits of which can accrue to either party. Such policies may impose additional costs on incubating projects, leading to a decreased production of the OSS public good. Using the ASF Incubator policy documents, we construct a dataset that records who – ASF or an incubating project – bears the cost and who enjoys the benefit of each policy and procedure. We can code most policy statements as costing one party and benefiting one party. The distribution of costs and benefits according to party indicates whether the second-order actor is contributing to an increase in the public good and if they are doing so sustainably. Through a two-way ANOVA, we characterize the impact of ASF policies on the production of public goods (OSS). Being a part of ASF imposes some costs on projects, but these costs may make projects more sustainable. Our analysis shows that the distribution of costs and benefits is fairly symmetric between the ASF and incubating projects. Thus, the configuration of policies or the "institutional design" of the ASF could aid in producing the OSS public good by providing services that projects require.